Bar and beverage management - Arora, R. K. (New Delhi, 2009)
The bar and beverage industry is an emerging service industry. It consists of high level of market segment, huge variety of products, huge number of companies and many other characteristics. The global bar and beverage industry is a multi-billion dollar a year business. Like many other industries it is seeing a growing shift away from mature markets in North America and Europe to newer developing regions such as China, India and Russia. Managing a bar and beverage service is generally perceived to be a relatively simple job, but to those whose duty it is to make sure that their customers have an outstanding outing, employees don't disappear with the take, and owners maintain a steadily rising profit margin, the daily grind of running a bar is nothing compared to the tension that comes from trying to figure out how to take it to the next level. For successful outcomes, bar operations must be run by managers who have product and equipment knowledge, management savvy, marketing skills, insight into the latest trends, and, of course, a strong grasp of mixology.
Keywords: Bartending; Beverage